An Improved LMI-based Approach for the Design of Power System Damping Controllers⁎. Issue 25 (2018) - Bernardo, Raul T.; Oliveira, Ricardo C.L.F.; Dotta, Daniel
Abstract: This paper presents a less conservative LMI-based method for the coordinated design of robust decentralized damping controllers in the power systems context. The algorithm results from modifications made in a previous LMI design procedure widely explored in the literature. More precisely, slack variables are introduced in the synthesis procedures to remove structural constraints on the Lyapunov matrix, potentially reducing the conservativeness inherent in this type of approach. The advantage of the proposed technique is verified in an IEEE benchmark power system application and the designed controller performance is observed with eigenvalue analyses and non-linear time domain simulations.